The Effectiveness of the Know-Want-Learn Teaching Model in Improving Text Literacy in Upper Elementary School Students - Muhammad, Asrori (Advances in Social Sciences Research Journal, 2025)
This study aims to examine the effectiveness of the Know-Want-Learn Teaching Model to improve text literacy in upper elementary school students. The study was conducted using an experimental method with a one-group pretest-posttest design. The subjects of this study were fifth-grade students at Al-Azhar Islamic Elementary School in Pontianak, State Elementary School 2 in Mempawah, and State Elementary School 3 in Singkawang. There were four indicators of text literacy ability that were measured, namely (a) grasping the main ideas of the text, (b) describing the summary of the text orally, (c) describing the summary of the text in writing, and (d) formulating questions based on the text that has been read. The results of the study indicate that the Know-Want-Learn Teaching Model is effective in improving text literacy, especially in terms of grasping the main ideas of the text and describing the essence of the text orally, but it is not effective in terms of describing the essence of the text in writing and formulating questions based on the text that has been read.